Post-fire tree mortality in mixed forests of central Portugal - Catry, F. X.; Rego, F.; Moreira, F.; Fernandes, P. M.; Pausas, J. G. (Forest Ecology and Management, 2010)
Wildﬁres are a recurrent disturbance in the Mediterranean Basin. However, managers from this region are confronted with a lack of information on the effects of ﬁre on most woody species, which is required for deﬁning sustainable forest management strategies. Following a large wildﬁre in central Portugal (2003), we surveyed the area during the ﬁrst year and assessed the vegetative condition of 1040 burned trees from 11 different species. Among those trees, 755 individuals were selected and monitored annually for 4 years. At the end of the study, almost all the broadleaved trees survived, while most coniferous died. In spite of the low mortality observed in broadleaves, most were top-killed and regenerated only from basal resprouts, which implies a slow recovering process. Quercus suber, however, showed vigorous post-ﬁre crown resprouting and was the most resilient species. We ﬁtted logistic regression models to predict the probability of individual tree mortality and top-kill from ﬁre injury indicators and tree characteristics. Besides the differences between the two main functional groups (coniferous, broadleaved), bole char height and crown volume scorched or consumed were important predictors of tree responses. Additionally, the main factor determining crown mortality on broadleaved species was bark thickness. The selected models performed well when tested with independent data obtained on four other wild- ﬁres. These models have several potential applications and can be useful to managers making pre-ﬁre or post-ﬁre decisions in mixed forest stands in the western Mediterranean Basin.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Fire effects; Mediterranean ecosystems; Modelling; resprouting; Tree survival; Wildﬁres